Trx1 Gene Therapy Enhances Angiogenic Signaling and Reduces Ventricular Remodeling in the Infarcted Myocardium of Diabetic Rats - Samuel, Samson Mathews (2010)
BACKGROUND: The present study evaluates the reversal of diabetes mediated impairment of angiogenesis in myocardial infarction (MI) model of Type I diabetic rats by intramyocardial administration of adenoviral vector encoding Thioredoxin-1 (Ad.Trx1). Various studies have linked diabetes mediated impairment of angiogenesis to dysfunctional antioxidant systems in which Trx1 plays a central role. METHODS AND RESULTS: Ad.Trx1 was intramyocardially administered immediately after MI to non-diabetic and diabetic rats. Ad.LacZ was similarly administered to the respective control groups. The hearts were excised for molecular and immunohistochemical analysis at predetermined time points. The myocardial function was measured by echocardiography 30 days after the intervention. The Ad.Trx1 administered group exhibited reduced fibrosis, oxidative stress and cardiomyocyte and endothelial cell apoptosis as compared to diabetic MI group along with increased capillary and arteriolar density. Western blot and immunohistochemical analysis demonstrated myocardial overexpression of Trx1, HO-1, VEGF, p38MAPKβ and decreased p-JNK and p38MAPKα in the Ad.Trx1 treated diabetic group. Alternatively, we have observed significant reduction in the expression of VEGF in SnPP (HO-1 enzyme inhibitor) treated non-diabetic and diabetic animals even after Ad.Trx1 therapy. Echocardiographic analysis after 4 weeks of MI revealed significant improvement in the myocardial functional parameters such as the ejection fraction, fractional shortening and E/A ratio in the Ad.Trx1 administered group as compared to the diabetic MI group. CONCLUSION: We demonstrate that the infarcted myocardium can be rescued from diabetes related impairment of angiogenesis and reduce myocardial functional disorder by Trx1 gene therapy in streptozotocin induced diabetic rats.